The Prevalence of Bilateral Three-Rooted Mandibular First Molar in Indian Population - Karale, Rupali; Chikkamallaiah, Champa; Hegde, Jayshree; Aswathanarayana, Srirekha; Santhosh, Lekha; Bashetty, Kusum; Susheela, Shwetha Rajanna; Panchajanya, Srinivas (Iranian Endodontic Journal, 2013)
Introduction: The purpose of the present study was to evaluate the prevalence of bilateral three-rooted mandibular first and second molars in Indian population. Materials and Methods: A total of 215 patients were screened bilaterally for mandibular first and second molar and 430 samples of periapical radiographs were obtained. The gender, symmetry, and prevalence of three-rooted mandibular first and second molars were recorded. The correlation between left and right side occurrences and distribution were recorded and analysed using Z-test. Results: The results showed that 33 teeth had three-rooted mandibular first molars, 16 male and 17 female (P=0.442). Overall, 21 teeth of right jaw and 12 teeth of left jaw (P=0.103) showed presence of an extra-root. The prevalence of three-rooted mandibular first molars was 7.67% and second molar was 0.23%. The bilateral frequency distribution was 3.72% for the first molar. There was no statistically significant difference between right side and left side mandibular molars. Also, gender did not show a significant relationship with this variant. Conclusion: The endodontic treatments of first mandibular molars require a careful clinical approach in Indian population as a high racial prevalence of 7.67% three-rooted molars was found. However, in the same population, 0.23% mandibular second molars had three roots.